Peran Kepala Sekolah Dalam Peningkatan Kinerja Guru di SMKS Nurul Iman Ellak Daya Lenteng Sumenep - Mochlish Mochlish; Ahmad Budiyono (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2018)
Efforts to develop and improve teacher performance are basically an endless organizational need. This is caused by the development and improvement of performance not only if there is a gap between actual performance and expected performance, but also the development and improvement must continue to be done even though there is no gap. In fact, it should always be considered in order to experience continuous improvement. The purpose of this study is to describe the improvement of teacher performance, how the role of principals in improving teacher performance and what are the supporting and inhibiting factors of school principals in improving teacher performance. In this study shows that the role of school principals in improving teacher performance in SMKS Nurul Iman Ellak Sumenep Lenteng Power as follows: 1) Motivating work spirit, 2) Fostering discipline, 3) Giving awards, 4) Providing consultations, 5) Conducting class visits, 6) Demonstrate model attitudes and behaviors, 7) Develop the teaching profession. Meanwhile the supporting factors of school principals in improving teacher performance are: 1) Human resources, namely from the excitement and seriousness of the teachers to improve their performance, 2) Infrastructure facilities that are very helpful in improving teacher performance, such as lab space. computer, projector etc. meanwhile the inhibiting factors are: 1) incomplete infrastructure facilities such as sports fields and library rooms, 2) schools do not have independent funding sources such as school cooperatives.